Effect of Self Assessment System and Tax Collection on Value Added Tax Revenue (Case Study of Manado Primary Tax Service Office from 2019-2021) - CHRISTIAN, Theresia; KALANGI, Lintje; WANGKAR, Anneke (Journal of Governance, Taxation and Auditing, 2022)
Value Added Tax (VAT) is tax that imposed on every transaction of goods and services within the customs area. Self Assessment System of The tax collection system is applied to the central tax, namely Value Added Tax, the execution of this system is still not optimal that causing tax arrears. To solve this issue, the tax authorities collect taxes. The aim of this study is to determine and examine the effect of the Self Assessment System and Tax Collection on Value Added Tax Revenue at Manado Primary Tax Service Office. The population in this study is all time series data of VAT corporate tax payers at Manado Primary Tax Service Office. The sample in this study was 36 time series data units for 3 years (2019-2021). The sampling technique was carried out by purposive sampling and the data of this study used secondary data. Data analysis used multiple linear regression. The test results of this study indicate that the Self Assessment System has an effect on Value Added Tax Revenue, Tax Collection has an effect on Value Added Tax Revenue and Self Assessment System and Tax Collection simultaneously has an effect on Value Added Tax Revenue corporate tax payers at Manado Primary Tax Service Office in 2019 to 2021